Analisis Kelembagaan Pengelolaan Kawasan Jatinangor - Shafiera Amalia (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2015)
Jatinangor area is designated as an educational area. This area is growing rapidly now. Because of Jatinangor area is a part of Sumedang District, Sumedang’s local government has a big authority to manage this area. But, there are a lot of public service problems in this area, namely disorganized building development; limited health service; inadequate waste management sevices; inadequate water service, etc. The aims of this research are to describe about existing leadership; authority delegation; organization structure; coordination and budgeting Jatinangor area management. This Research used qualitative approach and descriptive method. Interview Technique was used to collect primary data. And purposive technique was used to choose the right informan for this research. Furthermore, this research used qualitative descriptive technique to analyse data. The result shows that the leader of Sumedang’s local government does not have big political will to manage Jatinangor Area. This affects organizational structure which manages the area. There is no specific agency to manage Jatinangor area. The management is conducted by common local government agencies. There are adequate coordination between Sumedang’s local government agencies and between Sumedang’s local government and West Java Province government. But, coordination between Sumedang’s local government agencies, university and society in Jatinangor area still are not adequate. Beside that, Sumedang’s local government does not provide sufficient funding to manage this area. This condition causes the public service in Jatinangor area is not optimal.